2019 International Conference on Robotics and Automation (ICRA) 2019
DOI: 10.1109/icra.2019.8793959
|View full text |Cite
|
Sign up to set email alerts
|

Improved Proximity, Contact, and Force Sensing via Optimization of Elastomer-Air Interface Geometry

Abstract: We describe a single fingertip-mounted sensing system for robot manipulation that provides proximity (pre-touch), contact detection (touch), and force sensing (post-touch). The sensor system consists of optical time-of-flight range measurement modules covered in a clear elastomer. Because the elastomer is clear, the sensor can detect and range nearby objects, as well as measure deformations caused by objects that are in contact with the sensor and thereby estimate the applied force. We examine how this sensor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…measurement [78]. They designed and evaluated different rubber shapes and optical configurations (flat rubber, rounded rubber, and light blocker configurations).…”
Section: ) Reflected Light Intensity-type Sensors (O-rli) Usingmentioning
confidence: 99%
“…measurement [78]. They designed and evaluated different rubber shapes and optical configurations (flat rubber, rounded rubber, and light blocker configurations).…”
Section: ) Reflected Light Intensity-type Sensors (O-rli) Usingmentioning
confidence: 99%
“…A compliant fingertip is coupled to the end of each finger by the distal joint. Each fingertip is constructed by embedding four optical proximity sensors into the rigid skeleton of the fingertip, and then encasing it inside of polydimethylsiloxane (PDMS) (Patel and Correll 2016;Lancaster et al 2019). Our previous work demonstrated that the distance measurements from the embedded proximity sensors provide sufficient sensory feedback to localize an object throughout in-hand manipulation (Lancaster et al 2022).…”
Section: Electrostatic Brake Enabled Handmentioning
confidence: 99%
“…al. [25] created a fingertip-mounted sensor that provides proximity, contact detection, and force sensing. Koyama et.…”
Section: Related Workmentioning
confidence: 99%